Macrophage fatty acid metabolism under chronic hypoxia shapes γδ T cell recruitment via CCL22 - Guerrero Ruiz, Vanesa M.; Khabaza, Aya; Bauer, Rebekka; Aliraj, Blerina; Mansouri, Siavash; Meyer, Sofie P.; Palmer, Megan A.; Winter, Hauke; Klotz, Laura Valentina; Elewa, Mohammed A. F.; Kur, Ivan M.; Angioni, Carlo; et al. (iScience, 2025)
Hypoxia in solid tumors is associated with poor outcomes because of metabolic adaptations that support tumor cell survival and alter immune cell function. However, the metabolic and phenotypic adaptations of macrophages (MФs) to chronic hypoxia (CH) remain unclear. This study identifies impaired activity of the oxygen-dependent enzyme stearoyl-CoA desaturase 1 (SCD1) as a driver of altered fatty acid (FA) metabolism in MФs under CH. SCD1 deletion enhanced pro-inflammatory gene expression while suppressing the production of the chemokine CCL22. We propose that attenuated SCD1 activity and an altered saturated fatty acids (SFA)/monounsaturated fatty acids (MUFA) ratio impair the function of the transcription factor HNF4α, thereby affecting the expression of inflammatory genes such as CCL22. Reduced CCL22 levels, in turn, impaired γδ T cell recruitment. Accordingly, CCL22 expression in non-small cell lung cancer patients correlated positively with γδ T cell frequency and patient survival. These findings highlight the immunometabolic role of SCD1 in the hypoxic tumor microenvironment.